Digital Contact tracing in the COVID-19 Pandemic: A tool far from reality. (August 2020) - Hegde, Ajay; Masthi, Ramesh
Digital contact tracing applications are being developed by governments across the world, to track and trace contacts. With little evidence, citizens are being forced and made to believe that it is an important step in pandemic control. We discuss briefly if contact tracing will be successful in the control of the Corona virus pandemic or is it just a tool governments are using to cover their helplessness.